1988
DOI: 10.1002/cber.19881210211
|View full text |Cite
|
Sign up to set email alerts
|

Neue Heterocyclisierungen mit Isocyaniden 2,3‐Diiminopyrrole; 4,5‐Diiminoimidazole und 1H‐Pyrrolo[2,3‐b]pyrazine

Abstract: Die Imidoylketenimine 1 bzw. dje im Grundsystem n i t 1 isomeren Vinylcarbodjimide 6 addieren Isocyanide zu den 2,3-Diiminopyr-New Heteroeydizatioas with Isocyanidcs. -f3-DiimmopyrroIeq 4,5-Diiminoimidrzdes and lH-Fyrro~o[2,34Jpyra~ rolen 3, die noch nicht besdirieben sind. Analog werden ausden Imidoylcarbodiimiden 12 und 'Ismyaniden die bisher noch nicht bekannten 4,S-Diiminoimidazple '13 gebildet. Die Imidazolsynthese durch Bildung der 1,5-imd 4,SBindungen ist neu. -Ein erstmalig isoliertes Divinylcarmiimid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
7
0

Year Published

1988
1988
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…1). The amino group of 6a forms an intramolecular H-bond with the O-atom of the amide CO group (N´´´O 2.573(2) , NÀH´´´O 145(2) 8) while the NH of the amide group forms an intramolecular H-bond with the 1-oxide O-atom (N´´´O 2.541(2) , NÀH´´´O 143(2) 8). Each interaction has a graph set of S(6) [17].…”
mentioning
confidence: 99%
“…1). The amino group of 6a forms an intramolecular H-bond with the O-atom of the amide CO group (N´´´O 2.573(2) , NÀH´´´O 145(2) 8) while the NH of the amide group forms an intramolecular H-bond with the 1-oxide O-atom (N´´´O 2.541(2) , NÀH´´´O 143(2) 8). Each interaction has a graph set of S(6) [17].…”
mentioning
confidence: 99%
“…Conversion of 3a to unprotonated of our knowledge, [1ϩ4] cycloadditions of this type have pyrrole 4a was readily carried out in CHCl 3 solution by been limited to the preparation of diiminopyrroles from im-treatment with triethylamine or aluminium oxide. Strucidoylketene imines [22] and the preparation of 1-aminoisoin-tural assignments of products 3a, 4a will be rationalized dole derivatives from 1,4-benzoquinone or naphthoqui-below. It is interesting to note at this point that they are at none [24] and 5,8-quinoxalinediones.…”
mentioning
confidence: 99%
“…[20] The uncatalyzed [1ϩ4] cycloadditions of N-arylketene imines, [21] vinyl carbodiimides, [22] and vinyl isocyanates [23] are also known to produce highly functionalized dihydroindoles and dihydropyrroles. About ten years ago, we found that the protonation of 1,3-diazabutadienes markedly increases their reactivity towards isocyanides.…”
mentioning
confidence: 99%
“…In 1988, Capuano and co-workers presented several examples of 2H-pyrrol-2-imines synthesis via the cyclization of vinylcarbodiimides with isocyanides that had different nitrogensubstituted groups (Scheme 1c). 5 Nevertheless, the lack of convenient access to vinylcarbodiimides and their instability in isolation and storage limit its further development.…”
mentioning
confidence: 99%